A life-course approach to understanding differential relevance of deviant peers for predicting cocaine/crack use - Wojciechowski, Thomas W. (Crime & delinquency, 2021)
Deviant peer association has been identified as a risk factor for cocaine/crack use. However, understanding is more limited regarding the stability in the salience of this effect across the life-course. The present study utilized the Pathways to Desistance data to test for variance in the magnitude of the relationship between deviant peer association and cocaine/crack use using mixed effects ordered logistic modeling. Results indicated that cocaine/crack use frequency varied as a quadratic function of time. The interactions between deviant peer association and age variables indicated that the magnitude of this relationship first declined during adolescence, but then increased during early adulthood. Implications are discussed.